Impact of Baseline Fatigue on a Physical Activity Intervention to Prevent Mobility Disability. Issue 3 (22nd December 2019) - Glynn, Nancy W.; Gmelin, Theresa; Santanasto, Adam J.; Lovato, Laura C.; Lange‐Maia, Brittney S.; Nicklas, Barbara J.; Fielding, Roger A.; Manini, Todd M.; Myers, Valerie H.; de Rekeneire, Nathalie; Spring, Bonnie J.; Pahor, Marco; et al.
Abstract : OBJECTIVES: Our aim was to examine the impacts of baseline fatigue on the effectiveness of a physical activity (PA) intervention to prevent major mobility disability (MMD) and persistent major mobility disability (PMMD) in participants from the Lifestyle Interventions and Independence for Elders (LIFE) study. DESIGN: Prospective cohort of individuals aged 65 years or older undergoing structured PA intervention or health education (HE) for a mean of 2.6 years. SETTING: LIFE was a multicenter eight‐site randomized trial that compared the efficacy of a structured PA intervention with an HE program in reducing the incidence of MMD. PARTICIPANTS: Study participants (N = 1591) at baseline were 78.9 ± 5.2 years of age, with low PA and at risk for mobility impairment. MEASUREMENTS: Self‐reported fatigue was assessed using the modified trait version of the Exercise‐Induced Feelings Inventory, a six‐question scale rating energy levels in the past week. Responses ranged from 0 (none of the time) to 5 (all of the time). Total score was calculated by averaging across questions; baseline fatigue was based on the median split: 2 or higher = more fatigue (N = 856) and lower than 2 = less fatigue (N = 735). Participants performed a usual‐paced 400‐m walk every 6 months. We defined incident MMD as the inability to walk 400‐m at follow‐up visits; PMMD was defined as two consecutive walk failures. Cox proportional hazard models quantified the risk of MMD and PMMD in PA vs HE stratified by baseline fatigue adjusted for covariates. RESULTS: Among those with higher baseline fatigue, PA participants had a 29% and 40% lower risk of MMD and PMMD, respectively, over the trial compared with HE (hazard ratio [HR] for MMD = .71; 95% confidence interval [CI] = .57‐.90; P = .004) and PMMD (HR = .60; 95% CI = .44‐.82; P = .001). For those with lower baseline fatigue, no group differences in MMD ( P = .36) or PMMD ( P = .82) were found. Results of baseline fatigue by intervention interaction was MMD ( P = .18) and PMMD ( P = .05). CONCLUSION: A long‐term moderate intensity PA intervention was particularly effective at preserving mobility in older adults with higher levels of baseline fatigue. J Am Geriatr Soc 68:619–624, 2020